A glucose-insulin-glucagon coupled model of the isoglycemic intravenous glucose infusion experiment - Subramanian, Vijaya; Bagger, Jonatan I.; Holst, Jens J.; Knop, Filip K.; Vilsbøll, Tina (Frontiers in Physiology, 2022)
Type 2 diabetes (T2D) is a pathophysiology that is characterized by insulin resistance, beta- and alpha-cell dysfunction. Mathematical models of various glucose challenge experiments have been developed to quantify the contribution of insulin and beta-cell dysfunction to the pathophysiology of T2D. There is a need for effective extended models that also capture the impact of alpha-cell dysregulation on T2D. In this paper a delay differential equation-based model is developed to describe the coupled glucose-insulin-glucagon dynamics in the isoglycemic intravenous glucose infusion (IIGI) experiment. As the glucose profile in IIGI is tailored to match that of a corresponding oral glucose tolerance test (OGTT), it provides a perfect method for studying hormone responses that are in the normal physiological domain and without the confounding effect of incretins and other gut mediated factors. The model was fit to IIGI data from individuals with and without T2D. Parameters related to glucagon action, suppression, and secretion as well as measures of insulin sensitivity, and glucose stimulated response were determined simultaneously. Significant impairment in glucose dependent glucagon suppression was observed in patients with T2D (duration of T2D:8(6-36) months) relative to weight matched control subjects (CS) without diabetes. Insulin action was significantly lower in patients with T2D and the Hill coefficient in the equation for glucose dependent insulin response was found to be significantly different in T2D patients relative to CS. Trends in parameters with respect to fasting plasma glucose, HbA1c and two-hour plasma glucose values are also presented. Significantly, a negative linear relationship is observed between the glucagon suppression parameter and the three markers for diabetes and is thus indicative of the role of glucagon in exacerbating the pathophysiology of diabetes.